Factors related to the incidence of pneumonia in toddlers at the Padang Guci Community Health Center, Kaur District, in 2022 - Supriani, Beti; Fauzi, Yusran; Wulandari, Wulandari (Journal of International Public Health, 2022)
Pneumonia is an acute infection caused by microorganisms such as viruses, fungi and bacteria. Microorganisms will then attack the lung tissue (alveoli). According to (WHO, 2020) pneumonia killed 740,180 children under the age of 5 years in 2019, accounting for 14% of all deaths in children under five years but 22% of all deaths in children aged 1 to 5 years. Pneumonia is the second cause of death after diarrhea in Indonesia. Patients with pneumonia under five in Indonesia in 2017 reached 447,431 cases (46.34%) and caused 1,351 deaths in under five (Ministry of Health RI, 2018). According to the 2018 Basic Health Research (Riskesdas), in 2013 in Bengkulu the prevalence of Pneumonia based on a NAKES diagnosis was 1.1% or around 45.3 thousand people and in 2018 it was 1.7% or around 70.0 thousand people. The Kaur District Health Office reported that the incidence of pneumonia in Kaur District in 2021 was 1,167 cases (Lap. ARI P2 Program of the Kaur District Health Office 2021). This study used a quantitative method with a cross-sectional research design. The population in this study were all mothers who had toddlers visiting the Padang Guci Health Center in Kaur District in 2022 from January to May with a total of 210. The sample used in this study was 68 respondents. The results of this study indicate that there is a relationship between the level of mother's knowledge and the incidence of pneumonia in toddlers at the Padang Guci Health Center in Kaur District in 2022, there is a relationship between the mother's attitude and the incidence of pneumonia in toddlers at the Padang Guci Health Center in Kaur District in 2022 and the relationship between mother's education and the incidence of pneumonia in toddlers in Padang Guci Health Center, Kaur District, in 2022. Suggestions can examine other risk factors that have not been identified and for the health center to provide education to mothers about the incidence of pneumonia, such as playing a video in the patient waiting room at the health center.